Christianity 2018: More African Christians and Counting Martyrs - Johnson, Todd M. (International bulletin of mission research, 2018)
This article features five statistical tables with 2018 figures for many aspects of global Christianity, from membership to finance to martyrdom. Over the last 1,000 years, Europe had more Christians than any other continent. By 2018 Africa had the most Christians: 599 million, vs. 597 million in Latin America and 550 million in Europe. At the same time, Christianity continues to decline in the Middle East, falling from 13.6 percent of the population in 1900 to less than 4 percent today. In 1800 Christians and Muslims together represented only 33 percent of the world's population; by 2018 they represented 57 percent, increasing to 64 percent by 2050.